Mainstream Culture Refocused Television Drama, Society, and the Production of Meaning in Reform-Era China - Zhong, Xueping (University of Hawai'i Press, 2010)
Serialized television drama (dianshiju), perhaps the most popular and influential cultural form in China, offers a wide, penetrating look at the tensions and contradictions of the post-revolutionary and pro-market period. Zhong Xueping's timely new work argues for recognizing the complexity of dianshiju's melodramatic mode and its various subgenres, in effect "refocusing" mainstream Chinese culture.Mainstream Culture Refocused explores the manifestations, in dianshiju, of issues of history and tradition; the cultural and ideological issues surrounding the notion of youth; and how women's emotions are represented in relation to their desire for "happiness." Song lyrics from music composed for television dramas are considered as "popular poetics" that express nostalgia and uncertainty, mirroring the social contradictions of the reform era.